Implementation of Nagoya Protocol and its Ethical Dilemma – the Case Study of Indonesia - Sukara, Endang; Ragamustari, Safendrri Komara; Sinaga, Ernawati (Bangladesh Journal of Bioethics, 2020)
Indonesia consists of more than 17,000 islands separated for hundreds of thousands of years making both the biodiversity and culture diverse. Strong connection between people and biodiversity form a vast array of traditional knowledges retaliated to the conservation and use of biological diversity. During the last 3 decades, tremendous advancement on science and technology has been able to uncover the intrinsic value of biodiversity. Many lead chemical compounds have been isolated and identified, and has opened up huge opportunities in developing new business based on biodiversity. International cooperation between Japan and Indonesia successfully isolated more than 1,000 species of actinomycetes from diverse ecosystems and more than 30% are new species. This group of microbe is important for future pharmaceutical industries. The consciousness on intrinsic value of biodiversity is, however, only being understood by countries having high science and technology capacity. The intrinsic value of biodiversity remains abstract to most of the people in the developing and less developed nations. The Convention on Biological Diversity (UN-CBD), Cartagena and Nagoya Protocol are legal documents to ensure conservation, sustainable use and sharing of the benefit from the utilization of biodiversity and its components. There is a high demand for the developed nations on access to biodiversity to uncover its benefit. The mechanism on access, fair and equitable sharing of the benefit from the utilization of biodiversity and its component are certainly full of ethical dilemma. For this, there is a great need for the developing country having rich biodiversity find the most appropriate way to manage biodiversity and traditional knowledge for their prosperity. Trust between countries rich in biodiversity and countries having high science and technology capacity is a crucial factor. Greater transparency and the recognition on comprehensive rights of people providing biodiversity is a key element in maintaining trust. Ethical standards cannot depend solely on rules or guidelines.